2012
DOI: 10.1002/asi.22609
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the landscape of research in information systems from the perspective of editorial boards: A scientometric study of 77 leading journals

Abstract: Characteristics of the Journal of the American Society for Information Science and Technology and 76 other journals listed in the Information Systems category of the Journal Citation Reports-Science edition 2009were analyzed. Besides reporting usual bibliographic indicators, we investigated the human cornerstone of any peer-reviewed journal: its editorial board. Demographic data about the 2,846 gatekeepers serving in information systems (IS) editorial boards were collected. We discuss various scientometric ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 71 publications
4
18
0
1
Order By: Relevance
“…The EAB sizes of IS journals vary from 15 to 93 with a mean value of 46.6 (Table 1), sizes consistent with those in Cabanac's (2012) study of 77 IS journals. The distribution of ABS scores for IS journals is not significantly different from that for the overall ABS set of journals (Chi = 2.75, p = 0.432), suggesting that in terms of ABS quality scores, IS journals are no more diverse than the general population of business and management journals.…”
Section: Findings Sample Demographicssupporting
confidence: 78%
See 1 more Smart Citation
“…The EAB sizes of IS journals vary from 15 to 93 with a mean value of 46.6 (Table 1), sizes consistent with those in Cabanac's (2012) study of 77 IS journals. The distribution of ABS scores for IS journals is not significantly different from that for the overall ABS set of journals (Chi = 2.75, p = 0.432), suggesting that in terms of ABS quality scores, IS journals are no more diverse than the general population of business and management journals.…”
Section: Findings Sample Demographicssupporting
confidence: 78%
“…Researchers have introduced a novel approach recently by using social network analysis (SNA) (Scott 2003, Wasserman andFaust 1999) to gain insight into the important aspect of journal governance Barabesi 2010, Burgess andShaw 2010). More recently EABs of information systems journals have been examined using scientometrics (Cabanac 2012) and SNA (Baccini and Barabesi 2011), although the latter study combined information and library sciences.…”
Section: Eabs Of Journals Are Important In the Context Of Diversitymentioning
confidence: 99%
“…Nowadays, authors have an interest in publishing in journals with the highest possible impact factor, and, therefore, it is reasonable to suppose that first-quartile journals accept more documents than fourth-quartile journals. This supposition bear out bear out previous work, like Cabanac (2012), stating that the range of papers accepted per journal is wider for the first-quartile than for the other quartiles.…”
Section: Questions Hypotheses and Resultsmentioning
confidence: 65%
“…However, Cho$et$al.,$p.$7" surveys in economics (Addis & Villa 2003;Green 1998), medicine (Galley & Colvin 2013;122" Keiser, Utzinger & Singer 2003), management (Metz & Harzing 2012), information systems 123" (Cabanac 2012), and anthropology (Stark et al 1997) have found comparable disparities in the 124" gender composition of editorial boards. Assuming the results for our focal journals are 125"…”
Section: "mentioning
confidence: 99%